A Review on Mechanical Behavior of Lithium Ion Batteries for Electric Vehicles - Sonali Sabale; Deepak Watvisave; Vishwajit Gaike (International Journal of Electro-Mechanics and Material Behaviour, 2024)
The current automobile industries are much dependent on conventional petroleum fuels like petrol, diesel etc. which are creating many environmental issues due to combustion reactions and generation of carbon dioxide. This continues use of conventional fuels leads to either increasing the price of it and vanishing of its resources in future. Considering this pure battery based electric vehicle or electric vehicle with hybridize combination of battery and any other energy storage sources can be used for automobile field. Batteries can be powered with electricity produced by renewable energy sources such as wind, solar, and others that are being wasted by human beings from many decades. Whereas hybridization can lead to shorten the harmful effects of petroleum fuels. There are different types of batteries are available for automobile field including lithium ion, lead acid, nickel bromide etc. which are used as per the specification considering efficiency parameters. These batteries are having significant advantages of storage of tremendous amount of energy in small units replacing the use of engine and zero / negligible combustion reaction. With many advantages these batteries has some drawback like thermal runaway, overcharging, sensitive to variation temperature and most important cost and disposal. The major Couse of these drawbacks depends on mechanical properties of battery. Mechanical deformation of battery leads to failure of separator, current collector which gives rise to initiation of electrode contact creating many thermal issues in battery cell or packs. The current seminar work focus on review of causes and effects of generation of mechanical deformation in battery and modes to reduce it by significant way in considering less or negligible effect on efficiency parameters. Four different sources of mechanical stress exerted on a battery implemented in a structure are examined in this study i.e. structural, thermal, fabrication and kinetics.
Keywords: battery; electric vehicles; mechanical deformation; thermal runaway